Anatomy and Physiology of Headache - Harriott, Andrea M.; Orlova, Yulia (Seminars in Neurology, 2022)
Headache disorders can produce recurrent, incapacitating pain. Migraine and cluster headache are notable for their ability to produce significant disability. The anatomy and physiology of headache disorders is fundamental to evolving treatment approaches and research priorities. Key concepts in headache mechanisms include activation and sensitization of trigeminovascular, brainstem, thalamic, and hypothalamic neurons; modulation of cortical brain regions; and activation of descending pain circuits. This review will examine the relevant anatomy of the trigeminal, brainstem, subcortical, and cortical brain regions and concepts related to the pathophysiology of migraine and cluster headache disorders.
Keywords: headache; trigeminovascular afferent; migraine; cluster headache